KARAKTERISTIK DAN STRATEGI INOVASI PENDIDIKAN - Khotima, Husnul; Sartika; Fajri Ismail; Karoma (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
A plan, technique, or sequence of actions intended to accomplish certain educational objectives is referred to as a strategy in the context of education. This essay aims to provide the idea of techniques for achieving certain learning objectives in a classroom setting. The research methodology used is library research, also known as literature study, which is a study that consults library study materials while examining a subject of interest. This research is characterized by descriptive analysis, which entails routinely analyzing the collected data and then offering clarification and insight to ensure the reader understands it fully.  The research results reveal that educational innovation strategies are one of the factors that determine the success and effectiveness of social change depending on the accuracy of strategy use.